Death, Christianity, and African Miners: Contesting Indirect Rule in the Zambian Copperbelt, 1935—1962 - Kalusa, Walima T. (The International journal of African historical studies, 2011)
[...] the spirits of the dead- whether Bemba or Bisa, Lozi or Luvale, Ngoni or Lunda, etc.- could find eternal rest, without the ritual intervention of backward-looking chiefs or their "tribal" representatives. [...] the beliefs and practices that converts create became central to the expression and definition of their own urban cultural and social identity.